Fundamentals of Aerospace Engineering - Arnedo, Manuel Soler (Open textbook library., 2017)
Fundamentals of Aerospace Engineering covers an undergraduate, introductory course to aeronautical engineering and aims at combining theory and practice to provide a comprehensive, thorough introduction to the fascinating, yet complex discipline of aerospace engineering. This book is the ulterior result of three year of teaching a course called Aerospace Engineering in the first year of a degree in aerospace engineering (with a minor in air navigation) at the Universidad Rey Juan Carlos, in Madrid, Spain.